Bio-intensive complimentary cropping systems for north-west India - WALIA, S S; GILL, R S; KAUR, TAMANPREET; AULAKH, C S (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during 2014–15 and 2015–16 at Punjab Agricultural University, Ludhiana to evaluate bio-intensive complementary cropping systems as a possible replacement of the prevailing rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system. The treatments comprised 12 cropping systems and were set in a three-time replicated randomized block design. The results revealed that maize (Zea mays L.) (cobs) + vegetable cowpea [Vigna unguiculata (L.) Walp.] + Sesbania-gram (Cicer arietinum L.) + gobhi sarson (Brassica napus L.) cropping system showed maximum rice equivalent yield (229.9 q/ha), production efficiency (79.4 kg/day/ha) and net returns (`30,6066/ha). These systems also ensured saving of 127.5 cm irrigation water over the existing rice-wheat system (247.5 cm) and proved to be a viable option to avail higher profitability for farmers in Punjab. The removal of N, P and K was significantly higher in all the maize based cropping systems over rice-wheat cropping system. In addition, maize (furrow) + turmeric (Curcuma longa L.) (bed)-wheat (bed) + linseed (Linum usitatissimum L.) (furrow) cropping system gave highest viable counts of actinomycetes and fungi, whereas maize (furrow) + turmeric (bed)-barley (Hordeum vulgare L.) (bed) + linseed (furrow) gave highest count for bacteria. The fodder based cropping system, viz. sorghum [Sorghum bicolor (L.) Moench] + cowpea (fodder)-wheat + gobhi sarson with high energy output showed the highest energy-use efficiency (48.28) and energy output efficiency (6.35×103 MJ/ha/day). Maize (cobs)+vegetable cowpea + Sesbania-gram + gobhi sarson cropping system showed the highest average maximum energy productivity (8.24 kg REY/MJ) and it was mainly due to its higher REY.